Happiness, Life Satisfaction and the Role of Work: Evidence from Two Australian Surveys - Dockery, A.M. (My University, 2003)
This paper investigates factors that influence Australians’ self-reported levels of happiness and life satisfaction with an emphasis on the role of labour market experience. The analysis is based on data from two surveys. The first, the 1995 Year 9 cohort of the Longitudinal Surveys of Australian Youth (LSAY), tracks a sample of young Australians in each year from Year 9 secondary school to age 19. The second is Wave 1 of the Household Income and Labour Dynamics in Australia Survey (HILDA). Ordered probit models are fitted to individuals’ ratings of how happy they are with their lives as a whole (LSAY) and their overall life satisfaction (HILDA). There is some evidence of declining levels of happiness with duration of unemployment. However, the results illustrate the importance the quality of working life, rather than just having a job, and some evidence on the influence of various job attributes on wellbeing is presented.
School of Economics and Finance, Curtin University of Technology, Working Paper
Keywords: Satisfaction; Employment; Satisfaction -- Life; Labour market; Employment and unemployment